Morphological evidence for modern human influences in late Central European Neandertals - Smith, Fred H; Lacy, Katherine M; Caldwell, Sarah J (Anthropologie, 2015)
The long-standing debate on the role of Neandertals in the emergence of modern humans in Eurasia has been partially resolved by the genetic indications of relatively small, but not insignificant, Neandertal contributions to modern Eurasian populations. The relatively small contributions of Neandertals to modern humans likely stems from demographic factors limiting Neandertal population sizes. One of the issues not addressed by the genetic data was the impact of early modern human immigrant populations on the late Neandertals inhabiting Eurasia between ~35,000 and 45,000 years ago. East Central Europe, the area of focus for most of Karel Valoch's work, provides evidence of late Neandertals from the sites of Vindija (Croatia) and Šipka and Kůlna (Czech Republic). Analysis of the fragmentary Vindija specimens demonstrates an anatomical pattern reflecting reduction in facial size and prognathism. This pattern is consistent in all individuals but is projected onto a total morphological pattern that remains Neandertal. The Kůlna 1 maxilla and Šipka mandible also demonstrate aspects of this mosaic. These specimens provide anatomical evidence that reflects some impact of early modern biology during, or perhaps even slightly before, the early phases of modern human migration into Europe. This evidence further supports the interpretation that population dynamics between Neandertals and early modern people were complex and likely variable in differing parts of the ranges in which these populations overlapped.
Keywords: Body Remains; Humans; akulturace; Europe; Jaw; Genome, Human; tělesné pozůstatky; Neanderthals; Population Dynamics; jeskyně; antropometrie; genom lidský; Anthropometry; Evropa; Caves; populační dynamika; Acculturation; lidé; čelisti; neandertálci